1999
DOI: 10.1111/1468-2338.00107
|View full text |Cite
|
Sign up to set email alerts
|

Transforming union women: the role of women trade union officials in union renewal

Abstract: The article investigates the nature of the increasing involvement of women in the decision-making structures of the fifth largest UK union through a study of senior women union officials. It is argued that senior union women, operating within a feminist paradigm, balance both transformational and status quo objectives in working towards union survival and renewal.It is uncontested that union survival depends on widening trade unions' traditional recruitment areas to include the service sector generally and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 8 publications
4
70
0
Order By: Relevance
“…This, in turn, has generated interest in the factors that shape leadership. Writers have variously emphasised the importance of generation and gender change, the role of factions and parties and the transfer of leadership styles from institutions beyond the labour movement (Darlington, 1998;Heery, 1996;Kelly, 1998;Kirton and Healy, 1999).…”
Section: Selectionmentioning
confidence: 99%
“…This, in turn, has generated interest in the factors that shape leadership. Writers have variously emphasised the importance of generation and gender change, the role of factions and parties and the transfer of leadership styles from institutions beyond the labour movement (Darlington, 1998;Heery, 1996;Kelly, 1998;Kirton and Healy, 1999).…”
Section: Selectionmentioning
confidence: 99%
“…Watson (1988) has identified the importance of significant others and significant events as catalysts for greater union involvement. Building on Watson (1988), Kirton and Healy (1999) identified as the gendered nature of such others and events and used significant gendered others and significant gendered events as analytical constructs. Although more recently Kirton (2003) has argued that "significant experiences" may be a more all-embracing term that encompasses a time dimension.…”
Section: The Gendered and Ethnicised Ordermentioning
confidence: 99%
“…This echoes earlier studies that have found that women who lead traditional lives are less likely to become representatives, whereas men leading traditional lives are not similarly constrained (Walton, 1991;Lawrence, 1994). This also emerges in Kirton and Healy (1999) where most senior union women were`atypical', as these are the women who are most able to give the necessary time, effort and commitment to trade union participation. Again, it could be argued that there is no point in building women's confidence to participate if the barriers to their participation remain in place.…”
Section: Childcare Issuesmentioning
confidence: 99%